Oxcabazepine (®Trileptal) in Anti-Epileptic Polytherapy - Peder Klosterskov Jensen (Behavioural Neurology)
The anti-epileptic activity of oxcarbazepine (OXC) was compared with that of carbamazepine (CBZ) and the primary active metabolite of OXC, a monohydroxy derivative (MHD). Altogether 255 patients receiving either OXC or MHD (192 and 63 patients respectively) were included in the analysis of efficacy. Out of these 255 patients a total of 40 were children. The duration of treatment varied between 8 and 24weeks. The daily dose of OXC or MHD varied between 600 and 5400 mg (in children 600–2400 mg). Out of five studies two were double-blind controlled studies (including a total of 105 patients) whereas the remaining three were open studies. The results of these studies indicate that, in adults with epilepsy, there is no statistically significant difference in overall seizure frequency between CBZ and OXC. In one double-blind study the number of generalized tonic-clonic seizures was significantly less frequent during treatment with OXC than with CBZ. No statistically significant difference with regard to side-effects was observed between OXC and CBZ. The results in children with epilepsy show a statistically significant difference in seizure frequency in favour of OXC, in comparison with CBZ. Overall, the polytherapy studies in adults and children support the effectiveness and safety of oxcarbazepine.